Cytotoxic effect of Streptococcus suis on peripheral white blood cells - Thananchai, Hathairat; Duangsonk, Kwanjit (Biomedical Sciences and Clinical Medicine, 2024)
Objective To investigate cytotoxicity of Streptococcus suis (S. suis) serotype 2 and serotype 14 isolated from healthy pigs, diseased pig and S. suis infected patients to peripheral blood mononuclear cells (PBMCs) and neutrophils. Method Cytotoxicity of S. suis to PBMCs or neutrophils were performed by measurement of lactate dehydrogenase (LDH) activity. Results The results demonstrated that live bacterial strains isolated from patients and their culture supernatants were found to be more cytotoxic to PBMCs than strains isolated from healthy pigs signifi cantly. Interestingly, the suilysin-negative strains were cytotoxic as the suilysin-positive strains, whereas heat-killed bacteria had little or no toxic effect on both types of leukocytes. In addition, cytotoxicity to neutrophils was also observed in some bacterial strains. Conclusion Our preliminary study showed that S. suis and their culture supernatant were toxic to both mononuclear cells and neutrophils. We postulated that the ability of bacteria to stimulate the secretion of proinfl ammatory cytokines from immune cells in combination with the ability to cause cell death which will result in the secretion of damageassociated molecular patterns (DAMPs) may be involved in streptococcal toxic shock syndrome (STSS) caused by S. suis infection. Since DAMP also stimulates the release of proinfl ammatory cytokines from immune cells.